PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, KOMITE AUDIT, DEWAN KOMISARIS, TERHADAP INTEGRITAS LAPORAN KEUANGAN - Mairiza Selvia; Dirvi Surya Abbas; Hesty Ervianni Zulaecha; Sigit Budi Santoso (Universitas 45 Surabaya, 2022)
The purpose of this study was to determine the effect of managerial ownership ,instutional ownership ,audit commitee,board of comiddioner on the itegrity of financial statments in companies in the basic and chemical industrysectors listed on the indonesia stock exchage(idx).The research period used was 3 years ,namely the 2018-221 period.The sampling technique used purposive samping technique.Bassed on the specified criteria,a sample of 20 companies was obtained from indoesian stock exchage website. The analytical method used is panel data regression analysis including the f test and t test processed using the eviews 9.0 program .The results show taht the board of comissioners has positve effect on the integrityof financial statements whereas ,managerial ownershp ,instutional ownership and the audit commitee have no effect on the integrity of financial statements. Keywords: , , , , .